Comparative Study Between Misoprostol And Oxytocin For Labor Induction In Term Pregnancy - حمود, مروة; ميسون ديوب; عصام الدالي (Latakia University Journal -Medical Sciences Series, 2023)
Ø  * Aim of the study: To know the effectiveness of misoprostol at a dose of 25 mcg vaginally every 4 hours in ripening the cervix and inducing labor in full-term births. Explain the complications that may occur during the induction. A comparison of misoprostol with oxytocin in terms of efficacy, complications, and neonatal effect * Patients and methods: This study was conducted on 100 pregnant women admitted to Tishreen University Hospital in Lattakia2021-2022,who fulfilled the study conditions and criteria.The patients were divided in two groups: The first group:It included 50 women who underwent induction of labor by Misoprostol vaginal administration The second group: It included 50 women who underwent induction of labor by oxytocin. * Results: The study included 100 patients whom were dividied in two groups. Group 1:50 patient whom used Misoprostol 25 mcg vaginally every 4 hours. Group 2:50 patient whom used oxytocins: The duration of induction is 17.2+-12.1 hours in the first group and 16.9+-9.8 hours in the secound. The rate of induction success is 94% in the first group, 96% in the secound. The rate of caesarean sectin is 8.5%in the first group and 8.3% in the secound The rate of fetal distress is 6.4% in the first group and 6.25% in the secound The success of induction was higher in both groups with increassed cervical maturity The success rate of induction was higher in multiple The rate of caesarean sections and fetal distress was higher in first pregnancy *Conclusion: Use of Mesoprostol to induction of labor at term of pregnancy showed results similar to oxytocin in terms of mean duration of induction,success of labor induction ,frequency of caesarean section and fetal distress.